The Influence of the Blended Learning Model on Student Learning Outcomes in the Ornamental Plants Agribusiness Subject Class XI ATPH SMK Negeri 4 Gowa - Putri, Alvira; Kaseng, Ernawati Syahruddin; Yanto, Subari (Formosa Journal of Applied Sciences, 2024)
The research carried out aims to evaluate student learning achievements through the Blended Learning model approach in the Ornamental Plant Agribusiness subject. The population for this research was all students in class XI ATPH consisting of four classes. The research sample was class XI ATPH 1 as the experimental class and class XI ATPH 4 as the control class, each with 23 students. Data was obtained through pretest and posttest before and after learning to measure student learning outcomes regarding material related to requirements for ornamental plant growing media. The results of the analysis show that the pretest average for the experimental group is 37.39 and the control group is 36.74. The posttest average for the experimental group increased to 80.65 while the control group became 65.87. The experimental class has an average N-Gain of 0.69, higher than the control class, which has an average N-Gain of 0.45.